Characteristics of pyrolysis products from pyrolysis and co-pyrolysis of rubber wood and oil palm trunk biomass for biofuel and value-added applications. Issue 6 (December 2020) - Sakulkit, Patipan; Palamanit, Arkom; Dejchanchaiwong, Racha; Reubroycharoen, Prasert
Graphical abstract: Highlights: Pyrolysis and co-pyrolysis of RWS and OPT by using moving bed reactor were studied. Yield and characteristics of bio-oil, biochar and gas were determined and analyzed. Bio-oil from RWS was better than those from OPT and RWS mixed with OPT. Co-pyrolysis enhanced yield and quality of bio-oil, biochar and gas. RWS and OPT are challenging feedstocks for pyrolysis and co-pyrolysis. Abstract: This study investigated the yields and characteristics of bio-oil, biochar and pyrolysis gas obtained from pyrolysis and co-pyrolysis of rubber wood sawdust (RWS) and oil palm trunk (OPT) by using an agitated bed pyrolysis reactor. Co-pyrolysis of RWS and OPT was performed at the mixing ratio of 50:50 (wt.). The biomass samples were pyrolyzed at temperatures of 400, 450, and 500 °C under specific conditions. The results indicated that the yields of the bio-oil, biochar and pyrolysis gas were in the ranges of 38.5-46.5, 22.27-28.68 and 30.1-36.9 wt.%, respectively. Pyrolysis of RWS at 500 °C provided the most bio-oil. Co-pyrolysis of RWS and OPT could improve the product yield and quality. The bio-oil had relatively high water content, while its pH was low. The main compounds of bio-oil were oxygenated compounds such as acetic acid, phenols and 2-Propanone, 1-hydroxy-, determined by GC-MS. The higher heating value (HHV) of bio-oil ranged from 16.1 to 20.36 MJ/kg. The biochar had high carbon content and low oxygen content in proximate and ultimate analysis, and based on FTIR. The HHV of biochar was in the range from 26.35 to 29.6 MJ/kg. The biochar also was highly porous, which was revealed by SEM and BET. The pyrolysis gas mainly contained CO, CO2, H2 and CH4, and its heating value was in the range from 3.23 to 6.7 MJ/m 3 . Based on these results, the RWS and OPT are alternative and challenging biomasses for conversion to biofuels and value-added products via pyrolysis.